2012
DOI: 10.9790/3013-24103448
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the haemodynamic effects and seizure activity during modified ECT with thiopentone and propofol used as inducing agents.

Abstract: Abstract:--Electroconvulsive therapy is also known as Electroshock or Shock therapy or Electroplex.Seizure activity produced by ECT is considered as the therapeutic aspect of this form of treatment, but is accompanied by untoward physiologic consequences, mainly cardiovascular and cerebral in nature. The hemodynamic effects can have a significant impact in patients with underlying cardiovascular disease.The effects of certain anesthetic agents may render seizure activity difficult to generate,and the unmodifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…mean age, gender distribution, mean weight, ASA grade was statiscally significant. Studies conducted by Omprakash TM et al [10] , Kumar A et al [11] , Premendran B et al [12] , Mir AH et al [13] showed similar results as our study. Increase in the heart rate, SBP, DBP & MAP after ECT was observed in all 3 groups.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…mean age, gender distribution, mean weight, ASA grade was statiscally significant. Studies conducted by Omprakash TM et al [10] , Kumar A et al [11] , Premendran B et al [12] , Mir AH et al [13] showed similar results as our study. Increase in the heart rate, SBP, DBP & MAP after ECT was observed in all 3 groups.…”
Section: Resultssupporting
confidence: 91%
“…Mean duration of Anaesthesia was least in Propofol, had significantly earliest & smooth recovery (p<0.01) followed by Etomidate and Thiopentone. Rosa MA et al [18] , Premendran B et al [12] showed results concurrent with our study.…”
Section: Resultssupporting
confidence: 91%
“…In ECT, the main objective of general anaesthesia is to produce an unconscious state with muscle paralysis [4] . Recovery pattern, hemodynamic effects, activity of seizure, cognitive functions and cost effectiveness of the procedure is the choice of anaesthetic agent [5] . The present study evaluates and compares the effects of propofol and etomidate on recovery pattern, hemodynamic effects and activity of seizures in patients undergoing electroconvulsive therapy (ECT).…”
Section: Introductionmentioning
confidence: 99%